Effect of Chromatin-Remodeling Agents in Hepatic Differentiation of Rat Bone Marrow-Derived Mesenchymal Stem Cells In Vitro and In Vivo - Danna Ye; Tong Li; Philip Heraud; Rangsun Parnpai (Stem Cells International)
Epigenetic events, including covalent histone modifications and DNA methylation, play fundamental roles in the determination of lineage-specific gene expression and cell fates. The aim of this study was to determine whether the DNA methyltransferase inhibitor (DNMTi) 5-aza-2′-deoxycytidine (5-aza-dC) and the histone deacetylase inhibitor (HDACi) trichostatin A (TSA) promote the hepatic differentiation of rat bone marrow-derived mesenchymal stem cells (rBM-MSCs) and their therapeutic effect on liver damage. 1 μM TSA and 20 μM 5-aza-dC were added to standard hepatogenic medium especially at differentiation and maturation steps and their potential function on hepatic differentiation in vitro and in vivo was determined. Exposure of rBM-MSCs to 1 μM TSA at both the differentiation and maturation steps considerably improved hepatic differentiation. TSA enhanced the development of the hepatocyte shape, promoted the chronological expression of hepatocyte-specific markers, and improved hepatic functions. In contrast, treatment of rBM-MSCs with 20 μM 5-aza-dC alone or in combination with TSA was ineffective in improving hepatic differentiation in vitro. TSA and/or 5-aza-dC derived hepatocytes-like cells failed to improve the therapeutic potential in liver damage. We conclude that HDACis enhance hepatic differentiation in a time-dependent manner, while DNMTis do not induce the hepatic differentiation of rBM-MSCs in vitro. Their in vivo function needs further investigation.